PENGARUH PEMBERIAN PUDING GLIPO TERHADAP PERUBAHAN GLUKOSA DARAH PADA PASIEN DIABETES MELITUS RUMAH SAKIT TIMAH PANGKALPINANG - Izuddin, yana_180483; yuliana, yuliana; sadiq, ahmad (Poltekkes Kemenkes Bengkulu, 2025)
The prevalence of diabetes mellitus, a long-term disease characterized by elevated blood sugar levels, is increasing every year. When the pancreas stops producing enough insulin, it causes diabetes mellitus. Our aim at Bakti Timah Hospital Pangkalpinang was to find out how diabetics react to Glipo pudding in terms of fluctuations in their blood glucose levels. Research with an experimental design is what is meant by this. A paired t-test (dependent t-test) was used in the analysis of this data. The findings of the dependent t-test, which measures statistical differences, showed a mean difference of -21.5 mg/dL with a p-value of 0.05 (<0.05) between the treatment and comparison groups for the mean change in blood glucose levels. This indicates that the administration of flour pudding has an effect on blood glucose levels in patients with type 2 diabetes mellitus caused by soybean and purple sweet potato. Conclusion: Soybean flour and purple sweet potato pudding is high in energy and carbohydrates and changes blood glucose levels in diabetes mellitus patients at Bakti Tin Pangkalpinang Hospital.